Chitosan Supplementation Reduces Enteric Colonization of Campylobacter jejuni in Broiler Chickens and Down-Regulates Expression of Colonization Genes - Hanna R. Arambel; Ann M. Donoghue; Komala Arsi; Abhinav Upadhyay; Ann Woo-Ming; Pamela J. Blore; Kumar Venkitanarayanan; Dan J. Donoghue (Advances in Food Technology and Nutrition Sciences, 2015)
Campylobacter is one of the leading causes of foodborne bacterial gastroenteritis worldwide, and poultry is considered as the most common source of human infections. Cam-pylobacter is prevalent in most poultry flocks and a reduction of Campylobacter in poultry would greatly reduce the risk of campylobacteriosis in humans. Unfortunately, efforts to reduce Campylobacter in pre-harvest poultry have been met with limited success. Preliminary studies with the natural compound, chitosan, demonstrate its ability to kill Campylobacter, in vitro. The purpose of this study was to determine the ability of feed supplemented chitosan to reduce enteric Campylobacter colonization in broiler chickens. Additionally, the effect of chitosan on expression of Campylobacter’s chicken colonization genes was investigated using real-time quantitative PCR (RT-qPCR). Because chitosan’s antimicrobial properties may vary depending upon its molecular weight, selected doses of three molecular weight chitosans were supple-mented in the feed and evaluated for efficacy to reduce Campylobacter in chickens. Three replicate trials were conducted, and in each trial, birds were divided into 10 treatments (n=10 birds/treatment) and were fed 0% (controls), 0.25%, 0.5% or 1% (wt./wt.) of a low, medium or high molecular weight chitosan. Birds were fed treated feed for the duration of the study and orally challenged with a four-strain mixture of wild type C. jejuni on day 6. On day 15, the ceca samples were collected for enumeration of Campylobacter. In all three trials, the 0.5% dose of the medium molecular weight chitosan reduced cecal Campylobacter counts (P<0.05). RT-qPCR analysis revealed that chitosan down-regulated the expression of chicken colonization genes as compared to control (P<0.05). These results suggest that supplementation of chitosan in feed is a potential strategy to reduce the enteric colonization of Campylobacter in pre-harvest chickens.